Analisis Penerapan Sistem Usahatani Terintegrasi di Provinsi Bali - I Ketut Manu Mahatmayana (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2021)
Integrated Farming System (IFS) is a systems that combine livestock, aquaculture, agriculture and agro-industry in an expanded synergistic system, the waste of one process become the input for other process, with or without treatment to provide the means of production, such as energy, fertilizer, and feed for optimum productivity at minimum cost. There are two IFS models that implemented in Bali, integrated in unit at farmer (IFS unit) and integrated in area at group of farmer (IFS group). The level of implementation of IFS in both model is vary and it’s effect on farm income is still unknown. This study aimed to compare the performance of IFS model in farm unit and group. Analyse the factors that influance the performance of IFS. Analyze and compare the farm income and farm efficiency. Cross-secional data were collected from 67 farmer purposively selected. Descriptive analysis, analysis of farm income and R/C ratio were performed. The result indicated that the performance of IFS group model was higher than IFS unit model. The performance of IFS on both models were affected by farmers age, distance, farmers experience and road access. The income of IFS group model was higher and more efficient than IFS unit model. It’ imply that IFS should be applied to group model.